Instrumentalization of music in the late Ottoman Empire: The case of the Teutonia - Akyoldaş, Ayşe Seren. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis intends to perceive music as a medium being influenced by the political agenda of its epoch. In order to observe the use of music for political goals in the late Ottoman Empire, in the light of the archival materials, memoirs, newspapers, journals, and travel accounts, this thesis focuses on the evolution of the Western Classical Music in the Ottoman Empire. Having developed within the palace and then moved outwards through “catching up” with the Western ideals, the use of Western Classical Music will show that music had been perceived as an important part of the Ottoman Westernization process. In the second part of the thesis, the cultural performances, especially the musical activities, which were organized by the German Club Teutoina will be examined, where the political instrumentalization of music is again visible. Though economic imperialism in the Ottoman Empire has been dealt with by many economic historians, however, German cultural imperialism in the Ottoman Empire is underresearched. In order to fulfill this gap and challenge the conventional historiography regarding the position of the Ottoman Empire in terms of the German cultural imperialism, through the case of the German club in Ġstanbul, called the Teutonia, which was founded in 1847, German cultural imperialism in the Ottoman Empire will be discussed in details. Reading between the lines, this case study will prove how music had been instrumentalized for the political, cultural and social agendas of not only Germany, but also of the Ottoman Empire.|Keywords: instrumentalization of music, Western Classical Music in the Ottoman Empire, German cultural imperialism, the Teutonia.
Keywords: Germans -- Turkey -- History.; Germany -- Relations -- Turkey -- History.; Music -- Turkey -- History and criticism.